1373 Semi-Elective Trauma Patients Pathway and Medical Clerking Proforma, Closed Loop Audit. (12th October 2021) - Altell, T; Massa, E; Edwards, M
Abstract: Introduction: Semi-elective Trauma care is a service provided by the Trauma and Orthopaedic department for patients who sustain fractures to the upper and lower limbs requiring surgical intervention, are still ambulatory and can be cared for safely at home until the date of operation. Aim: To assess patients' referral pathway and clerking documentation against the Standards for the Clinical Structure and Content of Patient Records, published by the RCSEng. Method: We performed a closed loop audit on the clerking documentation and the referral pathway for these patients. We collected data retrospectively for three months, assessing the clerking documentation against the guidelines. The data was analysed and presented at our Clinical Governance meeting. We then implemented the Semi-Elective Trauma Pathway and the Medical Clerking Proforma. Afterwards, data was collected prospectively to complete the audit cycle. Results: A sum of 181 patient were included. Before the use of our changes, only 36% of patients had a complete clerking documentation, with two cases of near misses, and no comprehensive referral pathway for these patients. Post implementation of the Pathway and the Clerking Proforma, 88% of patients had complete clerking documentation, no near misses and 95% of them went properly through the pathway we introduced. Conclusions: These patients present an important part of any trauma list. This Audit shows that having a comprehensive referral pathway and a clerking proforma will make sure that patients will have full medical history taken and are ready for the operation on the day of surgery and decrease the number of near misses.